2013
DOI: 10.1002/adsc.201300421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Iodine‐Mediated Cascade Reaction of 2‐Alkynylbenzaldehyde and Indole: An Easy Access to Tetracyclic Indoloazulene Derivatives

Abstract: Abstract:The synthesis of iodo-substituted tetracyclic indole fused azulene derivatives was achieved from the reaction of 2-(substituted phenylethynyl)-benzaldehydes and different indoles in the presence of molecular iodine. The reaction involves the formation of a bisindole from the corresponding 2-(substituted phenylethynyl)benzaldehyde and indole followed by iodocyclization in a one-pot cascade process. A wide range of 2-(substituted phenylethynyl)-benzaldehydes and indoles were utilized in this protocol to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(4 citation statements)
references
References 68 publications
0
4
0
Order By: Relevance
“…A thorough literature survey provided us a clue that iodine-based compounds could enhance the overall conversion of the concerned reaction, as they show impressive catalytic activity in the formation of new C–C, C–O, and C–N bonds in organic compounds because of their electrophilic properties. , Hence, different iodine-based sources, such as potassium iodide (KI), tetrabutylammonium iodide (TBAI), N-Iodosuccinimide (NIS), and iodine (I 2 ), were investigated for this tandem oxidative cyclization reaction (Table S1). To our delight, we found that molecular I 2 , which has received considerable attention in recent years as an inexpensive, environmentally friendly, and readily available reagent to effect iodocyclization and cyclodehydroiodination reactions, worked quite well as an additive in this reaction, as it resulted in the maximum conversion of the employed reactants. The optimization studies showed that the addition of I 2 was crucial for cyclizing the model substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…A thorough literature survey provided us a clue that iodine-based compounds could enhance the overall conversion of the concerned reaction, as they show impressive catalytic activity in the formation of new C–C, C–O, and C–N bonds in organic compounds because of their electrophilic properties. , Hence, different iodine-based sources, such as potassium iodide (KI), tetrabutylammonium iodide (TBAI), N-Iodosuccinimide (NIS), and iodine (I 2 ), were investigated for this tandem oxidative cyclization reaction (Table S1). To our delight, we found that molecular I 2 , which has received considerable attention in recent years as an inexpensive, environmentally friendly, and readily available reagent to effect iodocyclization and cyclodehydroiodination reactions, worked quite well as an additive in this reaction, as it resulted in the maximum conversion of the employed reactants. The optimization studies showed that the addition of I 2 was crucial for cyclizing the model substrates.…”
Section: Results and Discussionmentioning
confidence: 99%
“…[155] Formation of bi-sindolesf rom aldehydes can also be promoted by iodine and therefore this element can be used in tandemp rocesses aimed at the preparation of polycyclic derivatives embedding two indole moieties (Scheme 78). [156] The recognizedm echanism for this transformation involves the preliminaryf ormation of bisindole 95 by reactiono fa ldehydes 94 with two equivalentso f indoles.T he bisindole is then converted into iodonium ion 96 which by as elective 7-endo-trig reactiona ffords the final products in satisfactory yields. The procedure involves addition of iodine in two distinct steps and utilization of triethylamine after the bisindole formationi sm andatory in order to ensure a complete cyclization reaction.…”
Section: C-2 Hydroindolationsmentioning
confidence: 99%
“…Cyclization reactions involving intramolecular nucleophilic displacements can be promoted by iodine . Formation of bisindoles from aldehydes can also be promoted by iodine and therefore this element can be used in tandem processes aimed at the preparation of polycyclic derivatives embedding two indole moieties (Scheme ) . The recognized mechanism for this transformation involves the preliminary formation of bisindole 95 by reaction of aldehydes 94 with two equivalents of indoles.…”
Section: Hydroindolation Of Alkynes and Allenesmentioning
confidence: 99%
“…Indoles and fused indoles have been repeatedly accessed by means of iodocyclization reactions, mainly involving the construction of the heterocyclic ring by CN bond formation16af or by C‐2 or C‐3 functionalization of preformed indole derivatives 16g,h. However, to the best of our knowledge, the strategy proposed herein represents the first iodocyclization approach toward building the homocyclic ring of polysubstituted indoles and complements other recently developed strategies, based on well‐established π‐activation catalysts (Au, Pt) 17.…”
Section: Introductionmentioning
confidence: 99%